2010
DOI: 10.1002/anie.201002191
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Regioselective Diels–Alder Reactions of Borylbenzynes: Synthesis of Functionalized Arylboronates

Abstract: B+[4+2]: 3‐Borylbenzynes undergo Diels–Alder reactions with substituted furans and pyrroles to give highly functionalized arylboronic acid derivatives with either good or exclusive regioselectivities (see picture). The effect of the boryl group on the regioselectivity arises from electronic rather than steric effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 72 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…In these cases, the reactive sites of the benzynes were completely controlled by the electron-withdrawing and electron-donating inductive effects of the C3-alkoxy and C3-boryl group, respectively. [68][69][70][71][72][73][74][75][76][77][78] The fluorination of 3-(tert-butyldimethylsilyl) benzyne 4f gave a mixture of meta-1f and ortho-1f in a 6.4 : 1 ratio under both batch and flow conditions (Entry 5). In this case, the regiochemistry is believed to be mainly controlled by the steric bulkiness of the C3-silyl group of 4f.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In these cases, the reactive sites of the benzynes were completely controlled by the electron-withdrawing and electron-donating inductive effects of the C3-alkoxy and C3-boryl group, respectively. [68][69][70][71][72][73][74][75][76][77][78] The fluorination of 3-(tert-butyldimethylsilyl) benzyne 4f gave a mixture of meta-1f and ortho-1f in a 6.4 : 1 ratio under both batch and flow conditions (Entry 5). In this case, the regiochemistry is believed to be mainly controlled by the steric bulkiness of the C3-silyl group of 4f.…”
Section: Resultsmentioning
confidence: 99%
“…In this case, the regiochemistry is believed to be mainly controlled by the steric bulkiness of the C3-silyl group of 4f. 68) Despite extensive examples in the literature involving the reactions of halobenzynes with a range of arynophiles, [79][80][81][82][83][84][85][86][87][88][89][90][91][92] the nucleophilic fluorination of halobenzynes 4h-4k, generated from 3h, 3i, 3j′, and 3k′, with Bu 4 NF(t-BuOH) 4 under normal batch conditions produced complex mixtures, and the yields of the expected fluorobenzenes 1 were very poor ( Table 3). In stark contrast, the reaction of 5-chloro-3-(tertbutyldimethylsilyl) benzyne (4h), generated from 3h, with Bu 4 NF(t-BuOH) 4 under the optimized flow conditions produced 1h in 51% yield as a mixture of two regioisomers (meta-1h/ortho-1h=1.2 : 1, Entry 1).…”
Section: Resultsmentioning
confidence: 99%
“…10,11 Herein, we present our very recent results on the regiocontrol of benzyne reactions using silyl 12,13a and boryl groups. 14,15 Given that the silyl and boryl substituents of the products can be converted into a variety of carbon , oxygen , and nitrogen substituents, the current method provides a new and reliable alternative means of synthesizing multisubstituted aromatic compounds. The mechanism underlying the regioselective reactions of the silyl and boryl benzynes is also discussed herein based on DFT calculations.…”
Section: Experimental and Theoretical Studies On Regiocontrol Of Benzmentioning
confidence: 99%
“…Elegant recent studies by Akai and co-workers on the unusual influence of 3-boryl substituents over the regioselectivity of benzyne capture stands as the only previous juxtaposition of aryne and boronate reactivities. [17] However,the requirement that the boronate be placed at the benzyne C3 position in these studies necessitated multistep preparation and revealed an incompatibility with fluoride in the absence of extremely robust protecting groups.…”
mentioning
confidence: 99%
“…Elegant recent studies by Akai and co-workers on the unusual influence of 3-boryl substituents over the regioselectivity of benzyne capture stands as the only previous juxtaposition of aryne and boronate reactivities. [17] However,the requirement that the boronate be placed at the benzyne C3 position in these studies necessitated multistep preparation and revealed an incompatibility with fluoride in the absence of extremely robust protecting groups. [17c] It also seemingly precluded use of the boronate prior to capture of the aryne and therefore the prospect of postfunctionalizing the aryne precursor.W e reasoned that the remarkable functional-group tolerance of iridium-catalyzed CÀHb orylation [18] and its preference for the least sterically hindered position of simple arenes [19] would provide ad irect way to introduce aB (pin) substituent selectively into precursors 1,t hereby preserving various R groups at C3, where they are known to influence aryne reactivity most profoundly.…”
mentioning
confidence: 99%